MixME: An R package to simulation‐test fisheries management robustness to mixed‐fisheries interactions - Matthew C. Pace; José A. A. De Oliveira; Simon H. Fischer; Paul J. Dolder (Methods in Ecology and Evolution)
Abstract Most fisheries on commercially fished species are managed on a stock‐by‐stock basis through catch limits. When set in isolation, catch limits ignore mixed‐fisheries interactions that result from catches by fishing fleets comprising multiple stocks, leading to quota imbalances with negative ecological and economic consequences. Tools are needed that efficiently account for mixed‐fisheries interactions and their impact on multiple stocks, paving the way for the development of mixed‐fisheries management approaches. Here, we introduce MixME, an R package for the simulation of management strategies in mixed fisheries considering technical interactions. Numeric optimisation techniques are used to implement catch‐limited fleet effort dynamics in continuous time. MixME can be applied to simple mixed‐fisheries forecasts as well as full‐feedback management strategy evaluation, with strict separation of observed and true system properties and a robust assessment of system uncertainty. We present an illustrative proof‐of‐concept application of MixME to a management strategy evaluation of existing single‐stock management of cod, haddock and whiting in the Celtic Sea. We demonstrate how it is not possible to achieve MSY‐based management of all stocks simultaneously in our case study mixed‐fishery system. Therefore, alternative management objectives must be considered. MixME enables performance testing of single‐stock and multi‐stock management against mixed‐fisheries constraints and supports the development of multi‐fleet management plans that better meet harvesting and conservation objectives for multiple stocks that are jointly exploited. We suggest that simulation testing against mixed‐fisheries constraints should be the de facto approach to developing management strategies for mixed fisheries.